2017
DOI: 10.1556/0806.44.2016.046
|View full text |Cite
|
Sign up to set email alerts
|

Combined zinc and nitrogen fertilization in different bread wheat genotypes grown under mediterranean conditions

Abstract: The combined application of nitrogen (N) and zinc (Zn) appears to be a promising agronomic strategy for the biofortification with Zn. To evaluate such efficiency, a field experiment was conducted in south-eastern Portugal under Zn-deficient soil. Four advanced breeding lines and two commercial varieties of bread wheat (Triticum aestivum L.) were fertilized with five treatments: i) control, ii) two foliar Zn applications, iii) one foliar Zn+N application, iv) soil and two foliar Zn applications, and v) soil and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…Wang et al ( 2012 ) found Zn concentrations in grains of wheat varied from 18.79 to 23.11 mg kg −1 in the control treatment of soil containing 0.78 mg kg −1 DTPA-Zn without soil Zn application. Gomez-Coronado et al ( 2017 ) reported grain Zn concentrations varied from 14.0 to 20.3 mg kg −1 when the DTPA-Zn was 0.28 mg kg −1 without soil Zn application, which is lower than 0.5 mg kg −1 DTPA-Zn as the widely recognized critical Zn level (Sims and Johnson, 1991 ). It is clear that the range of Zn concentrations between 34.9 and 47.7 mg kg −1 in the non-foliar Zn treated cultivars of this preset study (Table 3 ) is much higher than those obtained from Wang et al ( 2012 ) and Gomez-Coronado et al ( 2017 ), properly due to different wheat cultivars investigated and a high DTPA-Zn (1.5 mg kg −1 ) in combination with soil application of 30 kg ZnSO 4 ·7H 2 O ha −1 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Wang et al ( 2012 ) found Zn concentrations in grains of wheat varied from 18.79 to 23.11 mg kg −1 in the control treatment of soil containing 0.78 mg kg −1 DTPA-Zn without soil Zn application. Gomez-Coronado et al ( 2017 ) reported grain Zn concentrations varied from 14.0 to 20.3 mg kg −1 when the DTPA-Zn was 0.28 mg kg −1 without soil Zn application, which is lower than 0.5 mg kg −1 DTPA-Zn as the widely recognized critical Zn level (Sims and Johnson, 1991 ). It is clear that the range of Zn concentrations between 34.9 and 47.7 mg kg −1 in the non-foliar Zn treated cultivars of this preset study (Table 3 ) is much higher than those obtained from Wang et al ( 2012 ) and Gomez-Coronado et al ( 2017 ), properly due to different wheat cultivars investigated and a high DTPA-Zn (1.5 mg kg −1 ) in combination with soil application of 30 kg ZnSO 4 ·7H 2 O ha −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Gomez-Coronado et al ( 2017 ) reported grain Zn concentrations varied from 14.0 to 20.3 mg kg −1 when the DTPA-Zn was 0.28 mg kg −1 without soil Zn application, which is lower than 0.5 mg kg −1 DTPA-Zn as the widely recognized critical Zn level (Sims and Johnson, 1991 ). It is clear that the range of Zn concentrations between 34.9 and 47.7 mg kg −1 in the non-foliar Zn treated cultivars of this preset study (Table 3 ) is much higher than those obtained from Wang et al ( 2012 ) and Gomez-Coronado et al ( 2017 ), properly due to different wheat cultivars investigated and a high DTPA-Zn (1.5 mg kg −1 ) in combination with soil application of 30 kg ZnSO 4 ·7H 2 O ha −1 . In the location of Samsun with 1.59 mg kg −1 DTPA-Zn and Adana with 0.49 mg kg −1 , at the rate of 50 kg ha −1 of ZnSO 4 ·7H 2 O application to soil, Cakmak et al ( 2010a ) found grain Zn concentrations varied from 23 to 29 mg kg −1 and from 32 to 37 mg kg −1 in the controls without foliar Zn application, respectively, which indicated that a higher DTPA-Zn didn't necessarily lead to a higher grain Zn concentration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the main impacts on grain quality observed in the present study was the significant reduction in phytate in response to VNT1-D1 and VNT4-D2 and D3 ( Figure 4A). Substantial effort has been invested in (i) wheat cultivars with low phytic acid content in the grain (Guttieri et al, 2006;Ficco et al, 2009;Guo et al, 2015;Raboy, 2020) and (ii) biofortification to enhance Fe and Zn contents and availability in wheat grain (Hussain et al, 2012;Ramzani et al, 2016;Gomez-Coronado et al, 2017;Xia et al, 2018). A major contributor to Fe and Zn deficiencies in the human body is the abundance of phytates in food (Gharibzahedi and Jafari, 2017;Raboy, 2020), which are involved in chelating minerals, such as Zn and Fe (Xue et al, 2015).…”
Section: Grain Ionome and Phytate Concentrationsmentioning
confidence: 99%